Main directions of forming State strategy of sustainable regional development in Ukraine: realities and perspectives - Polovyan, O.V.; Kazakova, M.G. (Економіка промисловості, 2014)
Currently, Ukraine is facing the strategic task of economic modernization on the basis of sustainable development. One of the most popular methods of state regulation of sustainable development is a strategic planning system that balances economic, environmental and social goals of long-term community development. At the same time there is still no single approach to the definition, creation and development of an integrated strategy for sustainable development based on a holistic vision. The issue of sustainable development is especially important for Ukraine because of the high level of technogenic burden on its environment. The purpose of this research is to identify key principles, directions and features of a strategy for sustainable development of the regions of Ukraine. In the paper the influence of anthropogenic impact on the environment in Ukraine is analyzed. Using cluster analysis, the grouping of regions of Ukraine is made in terms of economic and environmental conditions. The rating analysis is carried out for the overall assessment of the economic and ecological situation in the regions of Ukraine. Research of regional development strategies of EU and Ukraine is conducted. According to its results Ukraine has no state strategy based on a holistic approach to solving the environmental problems of economic development. Existing documents highlight some aspects of sustainable development, but they are not complex. In its turn the analysis of the strategy "Europe 2020" confirms its holistic platform, complexity and focus on the coordination of social, economic and environmental objectives of society development. The authors of the paper suggest a number of directions for ensuring sustainable regional development in Ukraine. The practical implementation of the proposed recommendations will promote a process of changing qualitative characteristics of socio-economic systems within environmental constraints to provide opportunities to meet the needs of future generations.